Pengaruh Motivasi Kerja, Budaya Organisasi, Dan Gaya Kepemimpinan Transformasional Terhadap Komitmen Organisasi Dan Kinerja Karyawan (Studi Pada PT.Bank Pembangunan Daerah Kalsel Cabang Rantau) - Aulia Nurrahmi; Hairudinor Hairudinor; Setio Utomo (Universitas Lambung Mangkurat, 2020)
Every organization always has problems with human resources, so with the existence of these problems it is necessary to have high work motivation, organizational culture which is a reference for every leader and leader who has a transfrormational leadership pattern so that problems within the company can be overcome. This study aims to examine the effect of Work Motivation (X1), Organizational Culture (X2), and Transformational Leadership Style (X3) on Organizational Commitment (Y1) and Employee Performance (Y2) on PT. South Kalimantan Regional Development Bank Rantau Branch as many as 38 employees using sampling techniques saturated with quantitative method approaches. Data collection used a questionnaire while data analysis using Smart PLS Analysis.The results of this study in the form of Work Motivation (X 1 ) have a significant effect on Organizational Commitment (Y 1 ) with a large influence of 62, 3% are in the strong category, then Work Motivation (X 1 ) has a significant effect on Employee Performance (Y 2 ) with a large influence -27.6% are in a very weak category. Organizational Culture (X 2 ) has a significant effect on Organizational Commitment (Y 1 ) with a large influence 18.4% in the very weak category. Organizational Culture (X 1 ) has a significant effect on Employee Performance (Y 2 ) with a large influence of 26.8% in the weak category. Transformational leadership (X 3 ) has no significant effect on Organizational Commitment (Y 1 ) with a large influence of -3.4% in the very weak category. Transformational leadership (X 3 ) has a significant effect on Employee Performance (Y 2 ) with a large influence of -23 , 9% in the weak category and Organizational Commitment (Y 1 ) has a significant effect on Employee Performance (Y 2 ) with a large influence of -7.70% in the very weak category.Keywords: Work Motivation, Organizational Culture, Transformational Leadership Style, Organizational Commitment and Employee Performance